2022
DOI: 10.31958/jt.v25i2.5902
|View full text |Cite
|
Sign up to set email alerts
|

Development of E-Comic Based on Local Wisdom to Improve Scientific Literacy

Abstract: This research is the development of local wisdom-based e-comics to increase scientific literacy. Learning media can help achieve learning objectives. This study aims to develop e-comic learning media based on local wisdom to improve scientific literacy in grade IV elementary school. The type of research used is Research and Development with the ADDIE development model namely Analyze, Design, Development, Implementation, and Evaluation. This study used test subjects by carrying out validity tests on media exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…(5) Determine formative assessment techniques and instruments based on learning activities. (6) Creating a series of learning activities that are arranged systematically (7) learning activities are carried out in accordance with the learning objectives to be achieved by involving student activities according to the stages in the Project Based Learning (PjBL) model. (8) Attach assessment instruments in the form of checklists, rubrics or observation sheets as needed.…”
Section: Development Stagementioning
confidence: 99%
See 1 more Smart Citation
“…(5) Determine formative assessment techniques and instruments based on learning activities. (6) Creating a series of learning activities that are arranged systematically (7) learning activities are carried out in accordance with the learning objectives to be achieved by involving student activities according to the stages in the Project Based Learning (PjBL) model. (8) Attach assessment instruments in the form of checklists, rubrics or observation sheets as needed.…”
Section: Development Stagementioning
confidence: 99%
“…So it can be concluded that a learning device is a device that must be prepared by the teacher before carrying out learning in class (Permata Puspita Hapsari & Zulherman, 2021). In its implementation, the implementation of the Independent Curriculum prioritizes student activities, so a project-based approach is needed (Kurniawan et al, 2023). A project-based approach is usually called PjBL (Project Based Learning).…”
Section: Introductionmentioning
confidence: 99%
“…According to Arneson & Offerdahl (Priyangga et al, 2022), one of the main concepts of science is science learning because science continues to develop according to the conditions of the times. According to the Ministry of Education and Culture (2020), the objectives of learning science are to increase the intellectual ability to think at a higher level, solve problems systematically, achieve high learning outcomes, practice expressing ideas, and develop student characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, local wisdom is a form of belief, as well as customs from ancestors as a form of wisdom towards the environment in an area (Priyangga et al, 2022). Learning culture and local wisdom also improves students' higher order thinking skills.…”
Section: Introductionmentioning
confidence: 99%